ANALISIS HUKUM TERHADAP FUNGSI INSPEKTORAT DALAM PELAKSANAAN PENGAWASAN PENDIDIKAN DASAR DI KOTA MAKASSAR: LEGAL ANALYSIS OF THE FUNCTION OF THE INSPECTORATE IN THE IMPLEMENTATION OF BASIC EDUCATION SUPERVISION IN MAKASSAR CITY - Yonias Minggo, Stebit; Nur, Mustawa; Rusli, Muhammad (Clavia, 2021)
The purpose of this study was to determine the supervisory function of the Makassar City Regional Inspectorate in the implementation of basic education supervision in Makassar City. This research is a qualitative research. Where the type of data consists of primary data and secondary data, where primary data is obtained through interviews and direct observations in the field, while secondary data is obtained from data that has been collected by researchers through documents, books related to this research. The number of informants in this study amounted to 7 (seven) people. The data analysis technique used is descriptive qualitative analysis. The results of this study explain how the supervisory function of the Makassar City Regional Inspectorate in implementing the implementation of basic education in Makassar City, which includes a) inspection, where the inspection process carried out is well coordinated, b) repair, the form of repair carried out by the inspectorate Makassar City is in the form of a follow-up where the inspectorate provides an opportunity for the school to correct the mistake, but if it is not implemented then the inspectorate will provide a follow-up recommendation to the mayor who will then be given sanctions against the school, c) assessment, with the presence of the inspectorate in Supervising the implementation of basic education has a positive impact on schools because it provides a sense of caution for schools to use school budgets and implement them properly, which aims to educate the nation's children.